Inca evidence at the Chukurpus archaeological site. Upper basin of the Ica river - Quispe Orosco, José Luis (2021)
In this article we explain in a synthesized way part of the pre-Hispanic cultural process of the upper basin of the Ica river, with greater emphasis we treat the Late Intermediate Period (chukurpus) and Late Horizon (Inca) (1100 AD - 1532 AD). We specify the topics and evidence to determine changes in each period through the material correlate. The cultural elements, movable and immovable property, and the methods for the accumulation of empirical data, were the research instruments to define the diversity of cultural manifestations, exposed during the archaeological excavation at the Chukurpus Archaeological Site.